2020
DOI: 10.1262/jrd.2020-074
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency induces female infertile in order to failure of follicular development in mice

Abstract: Iron is important for many cellular functions, including ATP synthesis and cell proliferation. Insufficient of iron in the diet causes iron deficiency anemia (IDA), which often occurs in people living in the world. Since 50% of women with IDA show amenorrhea, the relationship of between iron deficiency and reproductive function was assessed using mice fed a low Fe diet (LFD). The estrous cycle in the LFD mice was blocked at diestrus, which impair follicle development, and fertility. Further, even LFD mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
0
14
0
1
Order By: Relevance
“…Our results demonstrate that increased duration of bleeding days associated with increased odds ratio for the primary infertility (Table 4), this may be a consequence to iron and mineral deficiency associated with bleeding; a finding reached by Gibson and colloquies as well as by Margarita et al, (21,22). This may be explained by the fact that iron loss, depresses ovarian functions, especially follicular development which results in infertility, this was shown in experimental mice study by Tonai and coworkers (23). Zhang et al, in China who did a large population prospective cohort study which concluded that both shorter (<4 days) and longer (>5 days) bleeding duration were associated with a lower fertility rate and longer time to pregnancy in rural Chinese women (24) these associations were unrelated to maternal age, ethnicity, education level, occupation, tobacco use, alcohol use and body mass index.…”
Section: Discussionmentioning
confidence: 93%
“…Our results demonstrate that increased duration of bleeding days associated with increased odds ratio for the primary infertility (Table 4), this may be a consequence to iron and mineral deficiency associated with bleeding; a finding reached by Gibson and colloquies as well as by Margarita et al, (21,22). This may be explained by the fact that iron loss, depresses ovarian functions, especially follicular development which results in infertility, this was shown in experimental mice study by Tonai and coworkers (23). Zhang et al, in China who did a large population prospective cohort study which concluded that both shorter (<4 days) and longer (>5 days) bleeding duration were associated with a lower fertility rate and longer time to pregnancy in rural Chinese women (24) these associations were unrelated to maternal age, ethnicity, education level, occupation, tobacco use, alcohol use and body mass index.…”
Section: Discussionmentioning
confidence: 93%
“…Tmprss6- null females possessed marked retardation in ovarian maturation ( 87 ), probably because of severe decrease in plasma iron levels. The defective ovarian follicle development and female infertility can be mimicked by a low iron diet ( 201 ).…”
Section: Multicellular Organisms Ii: Vertebratesmentioning
confidence: 99%
“…The Panel notes that according to the literature, iron plays an important role in male serum reproductive hormones, fertility and sexual function, although the extent to which perturbations in body iron levels may affect male reproductive health in the general population remains to be elucidated (Gabrielsen et al, 2018). The Panel also notes that, in females, the role of iron in reproductive fitness throughout the lifespan is extensively documented in the literature (Miller, 2016), and recent studies suggest the existence of an interplay between iron levels and hormonal status (Rossi et al, 2016;Tonai et al, 2020).…”
Section: Subchronic Toxicitymentioning
confidence: 99%